Aerosol emissions from a marine diesel engine running on different fuels and effects of exhaust gas cleaning measures. (1st January 2023) - Jeong, Seongho; Bendl, Jan; Saraji-Bozorgzad, Mohammad; Käfer, Uwe; Etzien, Uwe; Schade, Julian; Bauer, Martin; Jakobi, Gert; Orasche, Jürgen; Fisch, Kathrin; Cwierz, Paul P.; Rüger, Christopher P.; et al.
Abstract: The emissions of marine diesel engines have gained both global and regional attentions because of their impact on human health and climate change. To reduce ship emissions, the International Maritime Organization capped the fuel sulfur content of marine fuels. Consequently, either low-sulfur fuels or additional exhaust gas cleaning devices for the reduction in sulfur dioxide (SO2 ) emissions became mandatory. Although a wet scrubber reduces the amount of SO2 significantly, there is still a need to consider the reduction in particle emissions directly. We present data on the particle removal efficiency of a scrubber regarding particle number and mass concentration with different marine fuel types, marine gas oil, and two heavy fuel oils (HFOs). An open-loop sulfur scrubber was installed in the exhaust line of a marine diesel test engine. Fine particulate matter was comprehensively characterized in terms of its physical and chemical properties. The wet scrubber led up to a 40% reduction in particle number, whereas a reduction in particle mass emissions was not generally determined. We observed a shift in the size distribution by the scrubber to larger particle diameters when the engine was operated on conventional HFOs. The reduction in particle number concentrations and shift in particle size were caused by the coagulation of soot particles and formation/growing of sulfur-containing particles. Combining the scrubber with a wet electrostatic precipitator as an additional abatement system showed a reduction in particle number and mass emission factors by >98%. Therefore, the application of a wet scrubber for the after-treatment of marine fuel oil combustion will reduce SO2 emissions, but it does not substantially affect the number and mass concentration of respirable particulate matters. To reduce particle emission, the scrubber should be combined with additional abatement systems. Graphical abstract: Image 1 Highlights: High-sulfur fuel content led to high particle emissions. A wet scrubber efficiently reduced SO2 emission. Only minor reduction of particle emissions was accomplished by a wet scrubber. Coagulation and adding of sulfide/sulfate caused forming of larger particles. Reduction of particle emissions was obtained by adding an electrostatic precipitator.